SOCIOLOGY IN EARLY CHILDHOOD EDUCATION - Edimario dos Santos Souza, José; Tacyelle Santos Gomes, Heloísa; Maria da Silva, Aurineia; Paula Alves Pereira, Débora; dos Santos Lins, Givaldo; da Silva, Alex; Afonso Alves Geronimo, Manuel; Januário da Silva Araújo, Silvia; Santos Costa, Roseane; do Nascimento Prado, Roselândia (Revista Gênero e Interdisciplinaridade, 2024)
This article is due to bibliographic research and aims to ask the questions about the socialization of children in early childhood education and, more specifically, to understand aspects of the social construction of the so -called “student craft” at this level of education. It was intended to unravel the relationships involving early childhood education, families, children and their socialization. Starting from the assumption that there is currently a tendency in society to anticipate the schooling of the child and that this is related to both the transformations of the senses of childhood and “being a child” and specific social conditions, such as forms of family configuration , the division of labor between the sexes, the role of women and their place in the sphere of production, as well as the properly economic pressures about families. The theoretical contribution of this study lies in the interface of childhood sociology with the sociology of education. Thus, it was possible to highlight their commitments to awaken in children early attitudes of discipline and certain habits and knowledge to prepare it for the school and social “future”.